Association Between Primary Open Angle Glaucoma and Type II Diabetes Mellitus in Benghazi, Libya - Tahani Emgory; Anwar Gibril (AlQalam Journal of Medical and Applied Sciences, 2024)
Glaucoma, a leading cause of permanent blindness in the world, primarily affects older adults and is classified into four types, with diabetes mellitus potentially influencing the condition. The study aims to identify the link between Diabetes mellitus type two and Primary open angle Glaucoma. Subject and method A case-control study at Benghazi Educational Eye Hospital from December 2023 to February 2024. examined diabetic patients with and without glaucoma. Participants underwent ophthalmic examinations, including visual acuity, and gonioscopy. Patients with history of type two diabetes were included. The mean age of cases was significantly higher than controls [P=0.001]. There were significant differences in best corrected visual acuity between the two groups [P=0.035], Participants with high a [HbA1c] were more likely to have an advanced primary open angle glaucoma type. Participants with uncontrolled diabetes mellitus had higher intraocular pressure levels compared to the control group, [p=0.013]. There was a statistically significant difference in Retinal nerve fibers layers thickness in right eye, and Retinal nerve fibers layer thickness in left eye, between the case and control groups, [P= 0.041, 0.005 respectively. The age 66-75 years had a significantly higher risk of primary open angle glaucoma. A negative correlation between the duration of diabetes and Pattern standard deviation in left eye [ P = 0.051], as well as Visual Field left [P = 0.002]. The study reveals a significant link between diabetes mellitus type two and primary open angle glaucoma, with factors like higher intraocular pressure and older age causing higher incidence. early detection and management of risk factors could prevent or delay glaucoma onset. الجلوكوما، وهو السبب الرئيسي للعمى الدائم في العالم، يؤثر في المقام الأول على كبار السن ويتم تصنيفه إلى أربعة أنواع، مع احتمال تأثير داء السكري على الحالة. تهدف الدراسة إلى الكشف عن العلاقة بين مرض السكري من النوع الثاني [T2DM] والمياه الزرقاء ذات الزاوية المفتوحة [POAG]. من خلال فهم العلاقة بين مرض السكري و المياه الزرقاء، يمكن لمقدمي الرعاية الصحية تصميم خطط علاجية أفضل للمرضى الذين يعانون من كلتا الحالتين، مما قد يقلل من خطر فقدان البصر الدائم. هذه الدراسة لديها القدرة على تقديم نظرة ثاقبة لإدارة والوقاية من والمياه الزرقاء لدى الأفراد المصابين بالسكري. أجريت الدراسة في مستشفى بنغازي التعليمي للعيون في الفترة من ديسمبر 2023 إلى فبراير 2024. وشملت الدراسة مرضى المياه الزرقاء وأولئك الذين لا يعانون من المياه الزرقاء. خضع المشاركون لفحص كامل للعين، بما في ذلك حدة البصر تنظير الزوايا. وشملت معايير التشخيص التاريخ المبلغ عنه ذاتيا لمرض السكري، ومستوى الهيموجلوبين السكرى ، والجلوكوز في الدم العشوائي. كان متوسط العمر 65 عامًا، وكان متوسط عمر الحالات أعلى بكثير من الضوابط [الحالة = 63.85+7.، التحكم = 57.92+5.6.، P=0.001]. كانت هناك اختلافات كبيرة في أفضل حدة البصر المصححة بين المجموعتين [P = 0.035]، ولم تختلف مدة داء السكري بشكل كبير بين الحالات والضوابط، وكان المشاركون الذين لديهم مستويات أعلى من HbA1c أكثر عرضة للإصابة ب و المياه الزرقاء لمدة أطول. . كان لدى المشاركين المصابين بداء السكري مستويات أعلى من ضغط العين [IOP] مقارنة بالمجموعة الضابطة [ع = 0.013]. كان هناك اختلاف كبير في قيم BCVAL وCDRVR بين مجموعات الحالة الضوابط [P <0.05]. كان هناك فرق ذو دلالة إحصائية في RNFLTR وRNFLTL بين مجموعات الحالة الضوابط، [P = 0.041، 0.005 على التوالي. وكان عمر 66-75 سنة، أكثر عرضة لخطر الإصابة با المياه الزرقاء ذات الزاوية المفتوحة الأولية. وكان هناك ارتباط سلبي بين مدة العلاج مرض السكري وPSDL [P = 0.051]، وكذلك المجال البصري الأيسر [P = 0.002]. تكشف الدراسة عن وجود صلة كبيرة بين مرض السكري و المياه الزرقاء ، حيث تسبب عوامل مثل ارتفاع الضغط والتقدم في السن ارتفاع معدل الإصابة. ويشير إلى أن الاكتشاف المبكر وإدارة عوامل الخطر يمكن أن يمنع أو يؤخر ظهور والمياه الزرقاء.